Micro-structure and engineering behaviour of weakly bonded soil - Z. Ali Rahman; D.G. Toll; D. Gallipoli; M.R. Taha (Universiti Kebangsaan Malaysia, 2010)
This study was carried out to investigate the undrained behaviour of weakly bonded soil. Artificial specimens were used and were prepared from a mixture of sand and kaolin. The mixture was fired at 500¡C for 5 h to create uniform strength of artificial weakly bonding between sand particles. Based on microscopic observation of the specimens revealed that the fired kaolin formed bridges between the sand particles and most of the sand particles were entirely coated by kaolin. It was observed that very few sand grains made a direct grain to grain contact. The occurrences of inter-particle voids either isolated or connected to form larger voids. Fissures found in between the bonding and the grains were due to high temperature firing. A series of consolidated undrained tests (CU) were performed using conventional triaxial compression test. The stress ratio curves for the bonded specimens showed a significant peak at early strain and the values of maximum stress ratios dropped with increasing applied confining stresses. For the destructured (or unbounded) specimens, no apparent peaks were observed and the stress values were slightly lower compared to that of bonded specimens. The bounding surface for the destructured specimens is represented by a straight line equivalent to stress ratio of 1.24. This line is equivalent to strength parameters of internal friction angle, φ’ and cohesion intercept, c’ of 31o and 21 kPa, respectively. Meanwhile, the bounding surface for the bonded specimens is indicated by some curvature at low stress (p′<150 kPa) and high stresses (p′>1100 kPa). The study clearly suggested the role of bonding on the engineering behaviour of residual soils in undrained conditions.